Efektivitas Model Problem Based Learning Berbantuan LKPD terhadap Hasil Belajar Muatan Pelajaran Ipa di SD Muhammadiyah Wirobrajan I - Muhamad Ikhwan Nugraha; Beny Dwi Lukitoaji (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2024)
The problem of this research is an effort to prove the effectiveness of the LKPD-based learning model on science content learning outcomes at SD Muhammadiyah Wirobrajan I. This research method is a descriptive method, the form of research is classroom action research (PTK) and is collaborative in nature, the research subjects are teachers and class IV students SD Muhammadiyah Wirobrajan I, numbering 24 people. This research uses direct observation techniques, and uses test question sheets as a data collection tool. The research results are based on observations through effective science learning on student learning outcomes using the PBL method assisted by LKPD. This shows that the hypothesis which states that the implementation of PBL-based science learning assisted by LKPD in class IV of SD Muhammadiyah Wirobrajan I is effective in improving student learning outcomes.